The Law Enforcement in Indonesia: Progressive Legal Perspectives and Islamic Law - Hendrix Adinata; Nanik Prasetyoningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Many law enforcement in Indonesia adhere to a positivistic legal paradigm, namely interpreting the law textually from articles written in statutory regulations only. Meanwhile, in society, there are positive values and religious norms that are often ignored and violated in law enforcement. This normative juridical legal research aims to find out and analyze how law enforcement in Indonesia is viewed from the perspective of progressive law and Islamic law. The research results show that progressive law can be a solution and alternative for law enforcement that can reflect society's values of justice. To uphold the values of justice in society, law enforcement officials must have a progressive perspective that frees them from the shackles of legal formalities. Meanwhile, from the perspective of Islamic law, law enforcement is carried out using the ijtihad method to resolve the cases faced fairly and to satisfy the parties seeking justice. Ijtihad must be carried out by a mujtahid who has fulfilled the requirements and has the authority and competence to uphold Islamic law. Ijtihad is also a way to make Islamic law have the same characteristics as progressive law so that its existence can be accepted in every era, regardless of place.